Implementasi Batal Demi Hukum Dalam Perjanjian Kerja Menurut Undang-Undang Nomor 13 Tahun 2003 Tentang Ketenagakerjaan - Julianto; M. Soheh Salahudin W,; Muhammad Abdurrahman,; Alvin Reynaldo,; Reggy Permana, Husnaini (Consensus : Jurnal Ilmu Hukum, 2023)
The relationship between a worker and an employer after the contract of employment is called the employment relationship. An employment agreement can be made orally or by correspondence. How is a contract of employment contrary to the Employment Act No. 13 of 2003 considered void? Study of normative law is done. An employment agreement made as if it did not exist or does not exist juridically. However, most of the time, even though the job is considered legally void, workers or workers remain employed until their contracts expire.